2015
DOI: 10.1007/s00122-015-2593-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and analysis of a 20K SNP array for potato (Solanum tuberosum): an insight into the breeding history

Abstract: Key messageA 20K SNP array was developed and a comprehensive set of tetraploid cultivar was genotyped. This allowed us to identify footprints of the breeding history in contemporary breeding material such as identification of introgression segments, selection and founder signatures.AbstractA non-redundant subset of 15,138 previously identified SNPs and 4454 SNPs originating from the SolCAP project were combined into a 20k Infinium SNP array for genotyping a total of 569 potato genotypes. In this study we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
244
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(250 citation statements)
references
References 36 publications
2
244
0
4
Order By: Relevance
“…The genetic positions of markers were compared with their physical positions, as defined in Vos et al (2015). It was found that some markers did not map to the same chromosome as expected from the physical map; a list of such markers is included in Supporting Information, Table S1.…”
Section: Comparison Of Genetic and Physical Mapsmentioning
confidence: 99%
See 4 more Smart Citations
“…The genetic positions of markers were compared with their physical positions, as defined in Vos et al (2015). It was found that some markers did not map to the same chromosome as expected from the physical map; a list of such markers is included in Supporting Information, Table S1.…”
Section: Comparison Of Genetic and Physical Mapsmentioning
confidence: 99%
“…The concentration of DNA was measured using a NanoDrop ND-1000 Spectrophotometer (Thermo Scientific), and the DNA concentration was adjusted to 50 ng/ml (Vos et al 2015). For DNA concentrations in the range of 25-50 ng/ml, the sample also was used; samples having concentrations lower than 25 ng/ml were discarded, and DNA isolation was performed again.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
See 3 more Smart Citations